Genetic evaluation and variability studies on diverse marigold genotypes for vegetative and floral traits under Bihar conditions - Kumari, Dr Meenu; Kumari, Shiksha; Singh, Vijay Kumar; Singh, Deepti; Satyendra; Kesari, Ravi (Indian Journal of Horticulture, 2025)
A study of fifteen marigold genotypes was conducted to assess vegetative, floral, and seed-related traits, examining genetic parameters including variability, heritability, GCV, PCV, traits association, and path coefficient analysis, revealing substantial genetic variations between the genotypes, affecting multiple aspects of growth and flowering traits. Genotypes Arka Bhanu, Arka Vibha, Arka Shubha, Arka Abhi, Bidhan Marigold 1, and Pusa Bahar having good vegetative, floral and seed yield attributes. A diverse array of mean values was observed across all the evaluated traits, viz. plant height (42.32-74.80 cm), plant spread (12.58-72.49 cm), leaf biomass (32.62-822.2 g), flowering duration (33.67-92.67 days), and flower yield/ plant (119.46-569.8 g). Traits including leaf biomass, total carotenoids content, seed yield/ plant, chlorophyll content, flower yield/ plant, primary and secondary branching exhibited higher genotypic and phenotypic coefficients of variation. Heritability estimates exceeding 90% were observed for most traits, whereas plant height, days taken to first flowering, flower diameter, and days taken to seed maturation showed relatively lower heritability values. The genetic advance as of percentage mean varied widely, ranging from 22.60 to 224.90%. It was observed maximum for leaf biomass, total carotenoids content, seed yield/plant, total chlorophyll content, and flower yield/plant. The results suggest that these traits with maximum heritability and genetic gain can be used in crop improvement programme through hybridization.